The State and Your Hard-Earned Money : A Survey on Moral Perspectives in Public Finance - Mauro, Paolo (IMF Working Papers; Working Paper ;, 2021)
This note provides an overview of recent studies that have begun to investigate how differing moral perspectives shape attitudes toward tax and spending policies. Recent advances in evolutionary moral psychology and their application to survey-based economic analysis yield promising insights. Understanding the moral underpinnings of various groups' views may help policymakers design and make the case for measures that can muster broader support.